FORMULASI DAN UJI STABILITAS SEDIAAN SHAMPO HERBAL KOMBINASI EKSTRAK JERUK NIPIS (CITRUS AURANTIFOLIA) DAN PANDAN WANGI (PANDANUS AMARYLLIFOLIUS) - Devina Wahyu Astaning Cristy (ASSYIFA : Jurnal Ilmu Kesehatan, 2026)
This Study Focuses on the formulation and stability testing of a liquid herbal shampoo preparation that combines lime juice (Cutrus aurantifolia) and pandan leaf extract (pandanus amaryllifoliusa) as an anti -dandruff agent..The research method ultilized a laboratory experimental approach, covering the extraction of active ingredients, formulation with varying concentrations, and physical quality assessments, including organoleptic ,Homogeneity, pH , and foam stability tests. Physical evalution results over fourteen days demonstrated that the shampoo preparation maintained a stable consistency, remained homogeneous, and exhibited a pH value within the range of 4.6 to 5.0, which aligns with the physiological conditions of the human scalp . The Findings indicate that the combination of these ingredients provides a synergistic effect ini inhibiting the growth of dandruff-causing microbes while delivering a refreshing aroma.it is concluded that this liquid shampoo formulation meets the quality standards for cosmetic preparations and holds potential as a safe and effective hair care  alternative for long-term use.